ASSESSING THE ECONOMIC IMPACT OF INTEGRATING INTERNATIONAL PROTECTION BENEFICIARIES IN ROMANIA - Răzvan CÂRCIUMARU; Delia BEKESI (Annals of the University of Oradea: Economic Science)
The integration of beneficiaries of international protection is both a social and economic challenge for Romania. On the one hand, they can contribute to the budget and stimulate the economy through work and consumption, but on the other hand they require initial investment for integration. Studies show that effective integration can generate long-term economic benefits for host countries, but also that barriers such as access to the labour market, education or housing exist. Sound statistical data and relevant indicators are essential to inform policies. Integration is also a European priority, with the EU supporting inclusion through access to essential services. The costs of integration in Romania are estimated at 8000 euro/person annually and include accommodation, education, health. The materialized benefits indicate a contribution of over 4000 euros / year from a employed refugee. Financing in Romania comes mainly from EU funds such as AMIF or ERDF, non-reimbursable. National policy provides for measures such as training, reskilling and collaboration with Employment Agencies for Integration into the labour market. Global estimates indicate tax benefits of more than €110 million for 20 years after the integration of 100,000 refugees. Research shows mixed views on the economic impact, but also real difficulties in integrating into the labour market due to recognition of qualifications. Active policies and public-private partnerships are needed to increase employability and unlock the long-term potential of refugees